2011
DOI: 10.1080/2153599x.2011.647849
|View full text |Cite
|
Sign up to set email alerts
|

The need to believe: a neuroscience account of religion as a motivated process

Abstract: Religious belief has been shown to offer substantial benefits to its adherents, including improved well-being and health. We suggest that these benefits might be explained, at least in part, from a ''motivated meaning-making'' perspective. This model holds that people are motivated to create and sustain meaning (i.e., a sense of coherency between beliefs, goals, and perceptions of the environment, which provides individuals with the feeling that the world is an orderly place), and that religious beliefs buffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 131 publications
3
64
1
6
Order By: Relevance
“…Similarly, Inzlicht and colleagues (2011) found an association between religiousness (measured separately as religious zeal, belief in God, and religious attendance) and the ACC in a sample of religious undergraduates. Their findings indicated that religiousness buffered against error-related negativity (ERN) in the ACC, thus attenuating bodily states of distress.…”
Section: Factors Associating Adolescents’ Religiousness and Spiritualmentioning
confidence: 77%
“…Similarly, Inzlicht and colleagues (2011) found an association between religiousness (measured separately as religious zeal, belief in God, and religious attendance) and the ACC in a sample of religious undergraduates. Their findings indicated that religiousness buffered against error-related negativity (ERN) in the ACC, thus attenuating bodily states of distress.…”
Section: Factors Associating Adolescents’ Religiousness and Spiritualmentioning
confidence: 77%
“…TMT has played an invaluable role in illuminating the pervasive effects of mortality salience on human behaviors and some of the deeply rooted psychological functions served by significant aspects of our culture such as religion (e.g., Inzlicht, McGregor, Hirsh, & Nash, 2009;Inzlicht, Tullett, & Good, 2011;Norenzayan & Shariff, 2008), in-group bias/out-group prejudice (e.g., see Greenberg et al, 1990), and the objectification of women (e.g., Goldenberg, Heflick, Vaes, Motyl, & Greenberg, 2009;Goldenberg, Pyszczynski, Greenberg, & Solomon, 2000). Relatively recent developments in the field of social neuroscience, however, are enabling reevaluation-and refinement of theories such as TMT.…”
Section: Conclusion: a Revised Understanding Of Ms And Other Types Ofmentioning
confidence: 99%
“…The typical ERN signals have been observed as low in samples of believers and this low signals correlate with their high religious fervor or conviction. So, these results suggest that religious beliefs guard people against distress when facing uncertainty through controlled and automatic neurocognitive processes [wide explanations of these protocols and experiments can be found in Inzlicht et al (2009), Inzlicht and Tullett (2010), and Inzlicht et al (2013)]. A wide explanation of the Stroop task can be found in Mercadillo et al (2012).…”
mentioning
confidence: 99%